Rational design of aptamer switches with programmable pH response - Ian A. P. Thompson (Nature Portfolio, 2020)
Previous design strategies for pH sensitive aptamers were not readily tunable across pH ranges. Here the authors present a general method to convert aptamers into pH-responsive switches using two orthogonal motifs.